Utopia and socialism in the thought of Franz Hinkelammert, coordinates of marxism in the Global South - LEÓN DEL RÍO , Yohanka (Utopía y Praxis Latinoamericana, 2022)
The article presents a reflection on the key ideas in Franz Hinkelammert's work on utopia and socialism to identify coordinates of Marxism in the Global South. The critique of utopian reason and the significance of utopia, as well as the critique of real socialism and the significance of socialism; are linked in this work to show the comprehensiveness of dialectical analysis, as well as the scope and limits of critical thinking in function and at the service of a concrete humanism, and in commitment to the revolutionary transformative practice of the peoples of Our America.